2016
DOI: 10.1007/978-3-319-46478-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Design of Kernels in Convolutional Neural Networks for Image Classification

Abstract: Abstract. Despite the effectiveness of convolutional neural networks (CNNs) for image classification, our understanding of the effect of shape of convolution kernels on learned representations is limited. In this work, we explore and employ the relationship between shape of kernels which define receptive fields (RFs) in CNNs for learning of feature representations and image classification. For this purpose, we present a feature visualization method for visualization of pixel-wise classification score maps of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…We noticed that our quantitative model provides an explanation for the observation that some datasets are more sensitive to the kernel length than others, as shown by Sun et al [2016]. Additionally, we showed that our the scoring curve is strongly related to the model's performances.…”
Section: Discussionsupporting
confidence: 58%
“…We noticed that our quantitative model provides an explanation for the observation that some datasets are more sensitive to the kernel length than others, as shown by Sun et al [2016]. Additionally, we showed that our the scoring curve is strongly related to the model's performances.…”
Section: Discussionsupporting
confidence: 58%
“…However, when the existing models cannot meet our specific needs, we may not be allowed to customize a new architecture at the costs of heavy human works or numerous GPU hours [36]. Recently, the research community is soliciting innovative architecture-neutral CNN structures, e.g., SE blocks [14] and quasi-hexagonal kernels [30], which can be directly combined with various up-to-date architectures to improve the performance on our real-world applications.…”
Section: Introductionmentioning
confidence: 99%
“…The study [9] was carried out in computer implementation, not FPGA or embedded system implementation. Ample information on the importance of kernels CNN was provided by Sun et al [10]. In this paper, the authors debated on employing various types of kernels for different types of inputs provided and for multiple applications.…”
Section: Literature Surveymentioning
confidence: 99%